The Effect of Collaborative Learning Model on Improving PPKN Learning Outcomes and Social Attitudes in Elementary School Students - Nadia Salsabila; Diana Setiana; Wahyu Triono (FKIP - Universitas Riau, 2026)
This study investigates the effect of the collaborative learning model on improving PPKN (Civic Education) learning outcomes and social attitudes of fifth grade students at SDN 2 Kemantren, Cirebon Regency. The study employed a quasi experimental design with a pretest-posttest control group framework involving 30 students divided equally into an experimental group (n=15) and a control group (n=15). The collaborative learning model was implemented over four meetings during May 2026. Data were collected using a 20-item multiple-choice test for learning outcomes and an observation sheet for social attitudes. Instrument validity and reliability were confirmed using Pearson product-moment correlation, Cronbach's Alpha (α = 0.845), and Cohen's Kappa (κ = 0.807). Independent Samples T-Test showed significant differences in posttest scores for learning outcomes and social attitudes (p = 0.000). MANOVA also confirmed a significant simultaneous effect (F = 190.434, Wilks' Lambda = 0.066, p = 0.000, Partial η² = 0.934). N-Gain scores indicated moderately effective improvement in both variables. PPKN teachers at the elementary level are therefore encouraged to adopt collaborative learning as a core instructional strategy to simultaneously improve students’ academic achievement and social character formation.